To determine which of the given expressions results in an answer of 1, we can evaluate each option:
-
\( 13 - (7.42)^0 \):
- \((7.42)^0 = 1\)
- Thus, \( 13 - 1 = 12\) (not equal to 1).
-
\((-2.97)^0\):
- \((-2.97)^0 = 1\) (since any non-zero number raised to the power of 0 is 1).
-
\(5^0 + 9^0\):
- \(5^0 = 1\) and \(9^0 = 1\)
- Thus, \(1 + 1 = 2\) (not equal to 1).
-
\(3(8^0)\):
- \(8^0 = 1\)
- Thus, \(3 \times 1 = 3\) (not equal to 1).
From the evaluations, the expression that results in 1 is:
((-2.97)^0.